Juridical Analysis Of Creditor Protection Related To The Transfer Of Property In Bankruptcy Proceedings By Debtors - Rasji Rasji; Jeane Neltje Saly; Stefani Widyastuti (Publikasi Indonesia, 2023)
This study examines problems related to legal protection of creditors caused by debtors transferring their assets when applying for bankruptcy and regulations in the Bankruptcy Law so that they can become a legal umbrella for creditors to obtain their receivables. The research approach used in this study is a statutory approach (statue approach) with a type of normative juridical research. The sources of legal materials used are primary and secondary sources of legal materials. The technique of collecting legal materials used is library research. Validity uses theory triangulation and concept triangulation. The Bankruptcy Law essentially regulates in the event that debtors transfer their assets when they are filed for bankruptcy through a mechanism called Actio Pauliana. However, the Actio Pauliana mechanism contained in Article 41 of the Bankruptcy Law still has several shortcomings, including: First, Refusal due to differences in perception between judges to identify debtors' actions as fraud; Second, the judicial jurisdiction authorized to adjudicate Actio Pauliana's suit; Third, the lack of participation from parties, such as: customers, police, prosecutors, or banks due to incomprehension of the Bankruptcy Law.